The effects of radiative heat transfer during the melting process of a high temperature phase change material confined in a spherical shell. (15th January 2015) - Archibold, Antonio Ramos; Rahman, Muhammad M.; Yogi Goswami, D.; Stefanakos, Elias K.
Highlights: Analyzed effects of radiation heat transfer during melting in spherical shell. Performed analyses to ascertain the effects of optical thickness and the Planck, Grashof and Stefan numbers. Present correlations for melt fraction and modified Nusselt number. Abstract: The influence of radiation heat transfer during the phase change process of a storage material has been numerically analyzed in this study. Emphasis has been placed on the thermal characterization of a single constituent storage module rather than an entire storage system, in order to precisely capture the energy exchange contributions of all the fundamental heat transfer mechanisms during the melting of a phase change material (PCM) with tailored optical properties. The equations describing the conservation of mass, momentum and energy have been solved by using the control volume discretization approach, while the radiative transfer equation (RTE) was solved by the discrete ordinate method (DOM). The enthalpy–porosity method was used to track the PCM liquid/solid interface during the process. A parametric analysis has been performed in order to ascertain the effects of the optical thickness and the Planck, Grashof and Stefan numbers on the melting rate, as well as the total and radiative heat transfer rates at the inner surface of the shell. The results show that the presence of thermal radiation enhances the melting process. Correlations for the melt fraction and modified Nusselt number are developed for application in the design process of packed bed heat exchangers for latent heat thermal energy storage.